Effect of Prophylactic Steroid Therapy for Post Thyroidectomy Hypocalcemia - Akram, Junaid; Malik, Kamran Zamurrad; Ali, Muhammad; Tahir, Muhammad; Malik, Tehreem Ramzan; Adeel, Muhammad Umair (Journal of Rawalpindi Medical College, 2025)
Objective: The purpose of this study was to assess the effect of preoperative dexamethasone used to improve post-thyroidectomy hypocalcemia. Methods: This study was a Prospective clinical trial (Randomized) conducted in the department of Otorhinolaryngology, Tertiary care hospital, Quetta, for twenty-three months, i.e., from January 2023 till November 2024. 92 patients aged 18–60 with benign thyroid conditions and no preoperative hypocalcemia. Exclusion criteria were Graves’ disease, prior thyroid or neck surgery, and contraindications to corticosteroid use. Patients were arbitrarily allocated to the placebo (Group A) or dexamethasone (Group B) groups. Group B received 8 mg dexamethasone intravenously 60 minutes before anesthesia, while Group A received normal saline. Results: Postoperative hypocalcemia was more common in Group A (41% at 06 hours, 24% at 24 hours) compared to Group B (22% at 06 hours, 0% at 24 hours), with symptomatic hypocalcemia reported in 24% of Group A and none in Group B. Dexamethasone significantly reduced the incidence and severity of hypocalcemia, demonstrating its potential to improve early postoperative outcomes. Conclusion: Preoperative dexamethasone effectively reduces postoperative hypocalcemia and improves surgical outcomes in patients undergoing Total Thyroidectomy. Keywords: Dexamethasone, Goiter, Hypocalcemia, Postoperative Period, Thyroidectomy, Thyroid Diseases